Earth: the planet gone wild - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 1998)
The Earth produces of itself. Mark 4.28. 1. Planetary Aesthetics: Earth from Space. 2. The Wild Planet: Biological Beauty. 3. Wildlands and Wonder. 4. The Planet with Promise.
Lecture 1 was presented October 9, 1998 at the Carl Howie Lectures, Watts Chapel, Union-PSCE, Howie Center for Science, Art, and Theology, Union Theological Seminary, Richmond, Virginia.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.